Strategi Mempertahankan Semanggi sebagai Warisan Gastronomi Surabaya - Sutanto, Ken Kurniawan; Yahya, Ellen Lawrencia; Widodo, Yoseph Agung Priyo; Turgarini, Dewi (Jurnal Hospitality dan Pariwisata, 2024)
This research explores the disruption faced by Semanggi Surabaya, a legendary culinary icon, in the global era. Utilizing a qualitative case study approach with data triangulation, the study, from a nona helix perspective, aims to examine the viewpoints of various stakeholders regarding the exploration of Surabaya's culinary heritage, providing insights into preserving Semanggi. The findings acknowledge the declining trend and dynamic market shifts for Semanggi, highlighting the necessity for innovation in its conservation efforts. The study recommends leveraging information technology, optimizing marketing strategies, and reinforcing the unique values that define Semanggi Suroboyo to ensure its sustained legacy.